An Analysis of Certainly and Generally in Late-Modern English English History Texts - Álvarez-Gil, Francisco J. (Research in Language, 2019)
This paper analyses the adverbs certainly and generally as stancetaking markers. These adverbial devices are said to show authorial stance and to communicate the author’s commitment or detachment towards the information presented, and so they are classified as epistemic adverbs (Alonso-Almeida 2015). For this study, I have selected a corpus of history texts from the Modern English period (1700-1900), as compiled in The Corpus of History English Texts (Crespo and Moskowich 2015), on the basis of which the two evidential adverbs are examined using computer corpus tools, although manual inspection is also employed to assess the meaning of the items in context. The findings suggest that, in this type of scientific articles, the two adverbs are used with differing pragmatic functions, in the case of certainly it functions mostly as a booster and, in the specific case of generally, its use seems to primarily suggest a hedging purpose (Hyland 2005a).